Implementation of Project-Based Learning Models in 2D and 3D Animation Techniques to Improve Psychomotor Skills and Student Creativity of Class XI Multimedia SMK Negeri 3 Surakarta - Eliza Fadilah; Dwi Maryono; Endar Suprih Wihidayat (Journal of Informatics and Vocational Education, 2019)
The purpose of this study is to (1) Improve psychomotor skills of students in creating 2D animation with a project-based learning model; (2) Know the increase in creativity of students of class XI MM 2 of SMK Negeri 3 Surakarta by implementing a project-based learning model on 2D and 3D animation engineering subjects. This research is a Classroom Action Research conducted in 2 cycles. Subjects in this study were students of class XI MM 2 of SMK Negeri 3 Surakarta, amounting to 36 people. Data collection techniques used were observation, document review, practice tests, and portfolio assessments. The data validity test technique used is triangulation and the data analysis technique used is descriptive statistics. The results of the study stated that after the project-based learning model was applied, (1) the percentage of completeness of the results of the psychomotor skills test had increased by 41.67% in the pre-action, 63.89% in the first cycle, and 80.56% in the second cycle; (2) the creativity of students in terms of fluency, flexibility, authenticity, and elaboration has increased. Based on observations, students look more active and responsible in completing tasks. The conclusion of this study is the application of Project Based Learning models in 2D and 3D Animation subjects can improve psychomotor skills and creativity of students of Class XI MM 2 of SMK Negeri 3 Surakarta in 2018/2019 Academic Year.